2014
DOI: 10.4314/gjpas.v20i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electromagnetic waves produced by an amplitude modulation radio antenna on the electric power delivered by a silicon solar cell

Abstract: This article presents a one dimensional modeling of the influence of electromagnetic waves on the electric power delivered by a silicon solar cell under monochromatic illumination in steady state. The electromagnetic waves are produced by an amplitude modulation radio antenna of 2MW power of radiation and located at a variable distance of the solar cell [ [ +∞ , m 10. The magnetotransport and continuity equations of excess minority carriers are solved with boundary conditions and led to new analytical expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 1 publication
2
36
0
Order By: Relevance
“…A comparative study of the influence of electromagnetic field coming from AM and FM radio antennas on the power output and conversion efficiency of a silicon solar cell has been conducted by Zerbo et al [11]. For a given type of radio antenna, they obtained the same conclusion as for previous studies [9,10] but their study revealed that the FM radio antennas which produce low values of electromagnetic field have less influence on the solar cell than AM radio antennas.…”
Section: Effect Of Incidence Angle Varying From 0 Rad To π/2 Rad and mentioning
confidence: 91%
See 4 more Smart Citations
“…A comparative study of the influence of electromagnetic field coming from AM and FM radio antennas on the power output and conversion efficiency of a silicon solar cell has been conducted by Zerbo et al [11]. For a given type of radio antenna, they obtained the same conclusion as for previous studies [9,10] but their study revealed that the FM radio antennas which produce low values of electromagnetic field have less influence on the solar cell than AM radio antennas.…”
Section: Effect Of Incidence Angle Varying From 0 Rad To π/2 Rad and mentioning
confidence: 91%
“…They also observed an increase of the short-circuit photocurrent density and the leakage photocurrent density but a decrease of the open circuit voltage. In a related study, Zerbo et al [9] studied the effect radio waves on the power output and conversion efficiency of a silicon solar cell. The study conditions were same as in [10], except that this time the cells were illuminated by monochromatic light.…”
Section: Effect Of Incidence Angle Varying From 0 Rad To π/2 Rad and mentioning
confidence: 99%
See 3 more Smart Citations